Impak pengurusan sisa dan teknologi hijau terhadap prestasi projek: Kajian ke atas pihak berkepentingan dalam industri pembinaan di Malaysia - Nur Najihah, Osman (2017)
Nowadays, the construction industry development requires efficiency, productive, cost effective and environmental friendly. As a result, the government through the Construction Industry Development Board Malaysia (CIDB) in collaboration with stakeholders in construction industry have been implementing strategies such as developing the Construction Industry Transformation Programe (CITP) 2016-2020. One of the main thrusts is through environmental sustainability to achieve sustainable construction, and thus be a role model to other emerging nation. To realize this dream, every party in the construction industry should be aware and understand the concept of waste management, resource recovery and green technologies towards achieving sustainability in the construction industry. This research was focused on describing the waste management and green technology level of construction project in Malaysia, identifying the impact of waste management and green technology on the sustainability of construction projects in Malaysia and identifying the relationship between waste management and green technology on the construction project performance in Malaysia. The study population consisted of stakeholders (developers, contractors, consultants and clients) from construction projects around Malaysia. Information related to the stakeholders is obtained from the Real Estate and Housing Developers' Association Malaysia (REHDA), Construction Industry Development Board Malaysia (CIDB), Board of Architects Malaysia, Board of Quantity Surveyors Malaysia (BQSM) and Board of Engineers Malaysia. Questionnaires were distributed by post, e-mail and direct while visiting some of the respondent companies. This study received 101 respondents’ feedback from developers, contractors, consultants and customers. The research result shows how waste management and green technology have influenced a project’s success. Therefore, both of variables are positively related to projects’ performance. The results of this study, can be a guide to all the parties involved in the construction industry to improve level of waste management and green technology.